Respuesta :
Step 1: move all terms to one side
7 + 2x^2 - 10x = 0
Step 2: Use the quadratic formula
X = 10 + 2(square root of 11). 10-2 _/—-11
————————————. ——————
4. , 4
Step 3: Simplify solutions
X= 5 + (square root of 11) 5 - (square root 11)
——————————- , ————————
2. 2
7 + 2x^2 - 10x = 0
Step 2: Use the quadratic formula
X = 10 + 2(square root of 11). 10-2 _/—-11
————————————. ——————
4. , 4
Step 3: Simplify solutions
X= 5 + (square root of 11) 5 - (square root 11)
——————————- , ————————
2. 2
Answer:
Factor -2 out of the variable
Add 24/4 inside the parentheses and subtract 25/2
on the left side of the equation
White the perfect square trinomial as a binomial squared
Divide both sides by -2
Use the square root property of equality
Add 5/2 to both sides